“Analisis Regulasi Pesantren di Indonesia dalam Perspektif Peraturan Perundang-Undangan” - Siti Zaenab; Adinda Liana Putri; Yasira Salsabila (PT PUSTAKA CENDEKIA GROUP, 2026)
This study aims to analyze the regulations governing Islamic boarding schools (pesantren) in Indonesia and their role in supporting the implementation and development of pesantren as part of the national education system. This study employed a qualitative approach using library research methods. Data were collected from laws and regulations, books, and relevant scientific journal articles. The data were analyzed descriptively by examining various regulations related to pesantren. The findings indicate that the regulatory framework of pesantren in Indonesia is structured hierarchically, ranging from Law Number 18 of 2019 concerning Pesantren, Government Regulation Number 55 of 2007, Minister of Religious Affairs Regulation Number 30 of 2020, to technical policies issued by the Directorate of Diniyah Education and Islamic Boarding Schools. These regulations complement one another in providing legal recognition, guidance, and institutional development for pesantren. Keywords: pesantren regulation, Islamic education, educational policy, Islamic boarding schools.